Minor arcana. Volume one, The fool - Lemire, Jeff; Lemire, Jeff (Boom! Studios, a division of Boom Entertainment, Inc., 2025)
"Theresa's mother has fallen ill, and as a young bitter misanthrope, returning to her hometown to take care of her phony psychic of a mom is the last thing on Theresa's bucket list. But when Theresa finds out these abilities might be real after all, it will up to her to reconcile with her ailing mother, confront the failures of her past, and help the townsfolk she'd spent her life running from not so long ago... New York Times bestselling author Jeff Lemire (Descender, Black Hammer), garnering Eisner, Harvey, and Ignatz Awards and nominations for both written and illustrated works, as well as working with top talent like Andrea Sorrentino, Gabriel H. Walta, and Dustin Nguyen, debuts his first project at BOOM! Studios with this heart-gripping supernatural story about life, family, community, grief, mortality, and the power of human connection"--